Analysis of Long Noncoding RNAs in Choroid Neovascularization. (1st November 2020) - Zhang, Pengfei; Lu, Bing; Xu, Fengyuan; Wang, Chen; Zhang, Rongrong; Liu, Yinping; Wei, Chenghua; Mei, Lixin
ABSTRACT: Purpose : Choroidal neovascularization (CNV) is the major pathological features of wet age-related macular degeneration (AMD). Long noncoding RNAs play great roles in numerous biological processes. The purpose of the study was to investigate the expression profile and possible functions of the lncRNAs in CNV. Methods : In this study, the mice CNV model were conducted by laser photocoagulation. The expression profiles of lncRNAs were accessed by microarray analysis. Selected altered lncRNAs of mice CNV and wet AMD patients were validated by RT-PCR. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and lncRNA-mRNA coexpression network were conducted to reveal the biological functions. Results : The results revealed that 128 lncRNAs were significantly altered in RPE-choroid-sclera complexes of CNV mice ( P < .05, fold change > 2.0). GO analysis revealed that the altered target genes of the selected lncRNAs most enriched in angiogenesis. KEGG pathway analysis demonstrated that altered target genes of lncRNAs most enriched in focal adhesion signaling pathway. H19 was signiﬁcantly increased in the aqueous humor of wet AMD patients. Moreover, Inhibition of lncRNA H19 could suppresses M2 macrophage gene expression of laser-induced CNV mice. Conclusions : Our study identified differential expressions of lncRNAs in CNV, and lncRNA H19 might be novel potential target for the prevention and treatment of CNV.